Cancer nanomedicine: from PDGF targeted drug delivery - Rejeeth, Chandrababu (Royal Society of Chemistry, 2017)

(untitled) (Medchemcomm)
An innovative approach for the distinctively efficient action of smart targeted drug delivery to a specific cell type is obtained through the modification of the surface of nanoparticles. Specifically, the work identifies a cell surface receptor targeting drug delivery nanosystem based on mesoporous silica loaded with the anticancer drug cisplatin (cis-DDP) and poly-acrylic acid (PAA). A specific target is the PDGF receptors expressed in cervical cancer cells, thus making the PAA functionalized nanocomposite a suitable and promising nano-medicine for the targeting of PDGF-overexpressing cancers in the near future.